Relationships between prolonged neck/shoulder pain and sitting spinal posture in male and female adolescents - Straker, Leon; O'Sullivan, Peter; Smith, Anne; Perry, Mark (Elsevier Ltd, 2009)
Neck/shoulder pain (NSP) is a common problem for adolescents and posture has been suggested as an important risk factor.The aim of this cross sectional study was to examine the relationship between prolonged NSP and habitual sitting posture inadolescents.The habitual sitting postures of 1593, 14-year-old adolescents with and without prolonged NSP were assessed using sagittal planedigital photographs. Cervicothoracic and lumbopelvic posture angles were calculated from the digital images using motion analysissoftware. Adolescents reported experience of NSP by questionnaire. Differences between postures of males and females and thosewith and without prolonged NSP were examined using independent t-tests. The relationships between cervicothoracic and lumbopelvicpostures and presence of prolonged NSP were investigated using logistic regression models controlling for gender.Prolonged NSP was reported by 5.3% of the adolescents, with females reporting a higher prevalence rate (6.5%) than males(4.2%). Females also sat more erect with a more lordotic lumbar posture than males. Adolescents with prolonged NSP hadmore flexed cervicothoracic posture, more erect trunk and more lumbar lordosis. When gender was controlled, only lumbar lordosiswas related to the presence of prolonged NSP.